1994
DOI: 10.1056/nejm199406303302602
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Cyclosporine for the Treatment of Crohn's Disease

Abstract: In our patient population, the addition of low-dose cyclosporine to conventional treatment for Crohn's disease did not improve symptoms or reduce requirements for other forms of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…Cyclosporine has a beneficial therapeutic effect in patients with chronic active Crohn’s disease and resistance to or intolerance of corticosteroids [48,49,50] but none for maintenance therapy [51, 52]. The data on the safety of cyclosporine during pregnancy in humans is primarily derived from transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclosporine has a beneficial therapeutic effect in patients with chronic active Crohn’s disease and resistance to or intolerance of corticosteroids [48,49,50] but none for maintenance therapy [51, 52]. The data on the safety of cyclosporine during pregnancy in humans is primarily derived from transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…This may be an explanation of why medications such as infliximab are effective in some patients with UC (18) as well as in patients with CD (19). In addition, this may also be an explanation for the finding that other drugs such as cyclosporine with benefit in the acute phases of disease (20) do not have maintenance benefits (21) and why medications such as mercaptopurine become less effective with continued usage (22). As therapy for subtypes of IBD becomes more cytokine specific, it will be interesting to determine whether new-onset disease will respond differently than long-standing disease and which combinations or sequences of therapies should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies focused on short courses of high-dose intravenous CsA therapy, and have demonstrated impressive success for the treatment of fulminant colitis and the healing of refractory Crohn's disease fistulas. However, multiple attempts to convert high-dose CsA to an oral maintenance strategy, akin to the success in transplant immunosuppression, have paradoxically failed to demonstrate efficacy (5)(6)(7)(8)(9)(10)(11). The precise cellular and molecular mechanisms that underlie this lack of efficacy in the long term treatment of chronic intestinal inflammation have remained undefined, and may result from the emerging profile of adverse effects of CsA on nonimmune cell populations, including the vascular endothelium.…”
mentioning
confidence: 99%